Purple rice dessert product development by Quality Function Deployment technique and Mood Consumption concept - Wattanutchariya W. (2017)
© 2015 IEEE. Purple rice has been used for generations among northern Thai people as part of ancient wisdom in agricultural nutrition and primitive medical treatment. The objective of this research is to develop purple rice dessert products to satisfy customer requirements and to generally add value to the purple rice by Quality Function Deployment (QFD) technique and Mood Consumption concept. Questionnaires and in-depth interviews were conducted to collect customers' needs and to classify the customer into each mood consumption group. Then, QFD was implemented to transform customer requirements into technical specifications for each categorized consumer. The results showed that of all the product types, the important ratings were for price, package characteristics, and product's texture. In addition, Analytic Hierarchy Process (AHP) was implemented to identify proper packaging corresponding to each mood consumption group. Finally, the result of the product testing showed that the prototypes can satisfy the needs of consumers at a good level.